Na corda bamba: reforma psiquiátrica e saúde mental na atenção primária - Romanholi, Andréa Campos (2004)
This study discusses about the limits and possibilities of the Brazilian psychiatric reform implementation in the primary health care. Services on this issue have been assumed as a doorway to the Brazilian health system (SUS), however, they are not understood as part of the net of this system when it is concerning to people affected by madness. Trying to investigate that fact, this study has been worked with the primary health care professionals, through application of semi-structured interviews, questionnaires and focus group; so that, it was possible to get to know the difficulties and possibilities in order to transform that reality, and count on this service during the reform process. It could be assumed that, in the professionals point of view, the Basic Health Units have an important role in the psychiatric reform, once they are effectively territorial services, which allows one to get to know the users and their reality; and to accompany them throughout the several moments of their lives. However, those professionals reported several difficulties that make their possibilities to abandon the traditional practices of health extremely tough. They are very affected by the reality they face, by the excessive demand, and by the work process that is still bureaucratic and incoherent with the transformation proposals. Those difficulties refer to the attention to the general problems of the health field, and also interferes in the possibility to assume the attention of the people with mental problems that are seen as people who are required larger flexibility from the services to be attended. However, regardless the need of larger know-how, the mentioned difficulties are the same ones faced for the construction of a new model of attention to the health and the relationship with the mental health area is received in a positive way. About it, there are some expectations that this mentioned area, with its know-how and techniques, helps them to overcome difficulties. On the other hand, the work in the primary health care has shown a more complex reality than that which has being worked on the field of the reform. The last one deals with users who are victims of violence and exclusion that which is typical in the traditional psychiatric thought and in the primary health care there are those and more the enormous amount of people that suffer the violence of the social and economical exclusion, by living in poverty with lack of life perspectives and threatened by the informal but influential nets of the “local power” (coming from drug traffic and family violence). So, it is evaluated that the union of those two fields (psychiatry reformation and primary heath care) may enrich both, so that, it will cause the transformation of their practices and the enlargement of the invention opportunities.